2014
DOI: 10.12965/jer.140098
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sustained natural apophyseal glides on headache, duration and cervical function in women with cervicogenic headache

Abstract: The objective of this study is to investigate the effect of sustained natural apophyseal glides (SNAGs) on pain and headache duration in women with cervicogenic headache. The method of this study is a single blind and randomized controlled trial. Forty patients with headache were divided randomly into the SNAGs group (n= 20), and control group (n= 20). The expectation of this study was that the SNAGs group, with facilitatory glide, has full range of movement without pain. Sustained end range holds or overpress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(41 citation statements)
references
References 18 publications
1
40
0
Order By: Relevance
“…Another agreement with Eui-Ju Shin1 and Byoung-Hee Lee [33], who concluded that application of the SNAGs technique to middle-aged women with CGH is considered effective in decreasing the duration time of headache, and neck pain, as well as in development of neck function. Also, our finding is consistent with Miller et al [34], who stated in their systematic review regarding manual therapy and exercises for neck pain that combined mobilization and exercise had greater effect in reducing pain and improving functional abilitythan exercise only.…”
Section: Discussionsupporting
confidence: 69%
“…Another agreement with Eui-Ju Shin1 and Byoung-Hee Lee [33], who concluded that application of the SNAGs technique to middle-aged women with CGH is considered effective in decreasing the duration time of headache, and neck pain, as well as in development of neck function. Also, our finding is consistent with Miller et al [34], who stated in their systematic review regarding manual therapy and exercises for neck pain that combined mobilization and exercise had greater effect in reducing pain and improving functional abilitythan exercise only.…”
Section: Discussionsupporting
confidence: 69%
“…A total of 685 subjects were used in the 10 studies. The subject gender was a mixture of males and females in all studies except for Shin and Lee ( 22 ), which focused on a patient population of women with CEH. Borusiak et al ( 29 ) studied a sample of children and adolescents with CEH.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Many studies on the short-term effectiveness and manual therapy to the cervical spine (mobilization and manipulative therapy) have found it beneficial in reducing headache pain or disability ( 19 25 ), intensity ( 19 22 , 24 , 26 ), frequency ( 19 , 26 , 27 ), and duration ( 19 , 22 27 ). Therapeutic effects for CEH patients were also found in terms of improvement in neck pain and disability ( 17 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…We decided to implicate SHAM SNAG as an alternative control therapy, reducing the effect of confounding factors arising from conservative modalities and placebo effect applications. SHAM mobilization was a part of research protocols accounted for the need of ethical prepositions in clinical trials [22,56,57].…”
Section: Discussionmentioning
confidence: 99%